Amorphous NiCo2O4 decorated Pd/C as electrocatalysts for boosting ethanol oxidation reaction in alkaline media. (10th April 2022) - Wang, Meiling; Li, Dong; Jia, Wenyu; Zhao, Jin; Ma, Jianchun; Ma, Dongze; Tang, Tao; Hu, Tianjun; Jia, Jianfeng; Wu, Haishun
Highlights: Carbon-supported amorphous NiCo2 O4 decorated pd composite nanoparticles were successfully fabricated. Pd/NiCo2 O4 /C composite exhibits significantly enhanced electrocatalytic activity and excellent long-time stability for ethanol oxidation. Strong electron coupling between pd and NiCo2 O4 nanoparticles induces more electrochemical active centers by tailoring the electronic state of Pd. Amorphous NiCo2 O4 decorated Pd/C composites with plenty of oxygen defects may significantly facilitate the electron transfer. Well-dispersed nanoparticles and higher conductive carbon carrier with strong anchoring effect are also responsible for the superior catalytic performance. Abstract: The electrocatalytic efficiency and stability have become the most significant topics in the catalytic application of fuel cells. In this work, the carbon-supported amorphous NiCo2 O4 decorated Pd composite nanoparticles (Pd/NiCo2 O4 /C) was fabricated by means of the facile hydrothermal and reduction to investigate the electrocatalytic performance. The cyclicvoltammetry measurements show that the larger electrochemical active surface area (135.00 m 2 g −1 ), increased peak current density (160.99 mA cm −2 ) and lower onset potential (−0.70 V) are obtained in Pd/NiCo2 O4 /C catalysts compared to the commercial Pd/C with the Pd loading (10 wt.%), indicating that a significantly enhanced electrocatalytic activity for ethanol oxidation in Pd/NiCo2 O4 /C catalysts. More importantly, the Pd/NiCo2 O4 /C catalyst also presents the long-time stability during the ethanol oxidation reaction. The X-ray powder diffraction, X-ray photo-electron spectroscopy and transmission electron microscopy measurements were carried out to further demonstrate that there exists the strong chemical interaction between Pd and amorphous NiCo2 O4 nanoparticles, which leads to the formation of the more electrochemical active sites via redistributing the electronic structure of Pd and boosting anti-poisoning ability of intermediates. Our study provides a high-performance and promising electrocatalytic material, which can be applied to the direct ethanol fuel cells.